Technology-mediated teacher-researcher collaborations: Professional learning through co-design - Goldman, Susan; Gomoll, Andrea; Hmelo-Silver, Cindy; Hall, Allison; Ko, Monlin; Fortune, Angela; Kyza, Eleni A.; Agesilaou, Andria; Gomez, Kimberley; Gomez, Louis; Pressman, Emily; Rodela, Katherine; et al. (My University, 2019)
Collaborative co-design between teachers and researchers can provide the kinds of learning opportunities for teachers that lead to teacher agency, and flexible, adaptive, principled pedagogy. This symposium features four projects in which teachers and researchers engaged in technology-mediated collaboration to design inquiry-based learning environments to engage students in authentic disciplinary practices in a variety of content areas, including literary reading, literacy in mathematics, science, and engineering design. The size and scope of the collaborations vary, ranging from one-to-one to larger groups, as does the time span of the collaborations, providing opportunities to examine temporal affordances of technology supports. All four papers discuss collaborative co-design as sites of professional learning for teachers. We argue that these are excellent cases of CSCL and that they afford new insights into roles for technology in supporting and facilitating teacher and researcher learning.
Keywords: Computer aided instruction; E-learning; Literary reading; Professional learning; Technology support; Affordances